Three-dimensional "skin-framework" hybrid network as electroactive material platform for high-performance solid-state asymmetric supercapacitor. Issue 23 (26th April 2019) - Xia, Liaoyuan; Hu, Shaoheng; Zhang, Xueqin; Huang, Le; Liao, Yu; Qing, Yan; Wu, Yiqiang; Jiang, Wenping; Lu, Xihong
Abstract : 3D "skin-framework" architecture of the MCN with large interfacial contact area and high electrical conductivity enable it to serve as a powerful electroactive platform for high-performance solid-state MnO2 -MCN//AC-MCN ASC device. Abstract : Three-dimensional (3D) electrode materials are ideal candidates for use in fabricating high-performance supercapacitors (SCs), owing to their unique network structure and excellent electrochemical properties. In this study, an aerogel film produced by the freeze-drying self-aggregation of multiwall carbon nanotubes (MWCNTs) and cellulose nanofibers (CNFs) served as the "skin", and an inter-connected 3D network of nickel foam (NF) as the "framework", for the fabrication of an MWCNT/CNF-NF (called MCN) hybrid material with a distinct "skin-framework" architecture. Considering the metrics of excellent conductivity, high wettability, binder-free and unique 3D "skin-framework" structure, the MCN hybrid material has great potential as an electroactive material platform in constructing state-of-the-art asymmetric supercapacitor (ASC) electrodes. By incorporating MCN with electroactive manganese dioxide (MnO2 ) and active carbon (AC), MnO2 -MCN and AC-MCN composite electrodes with respective high areal capacitances of 1784.8 (equal to 469.7 F g −1 ) and 868.8 mF cm −2 (equal to 126.3 F g −1 ) at 5 mA cm −2 were successfully prepared. Further, both kinds of electrodes exhibited high charge/discharge ability rates and good cycle performance. Moreover, an optimally assembled MnO2 -MCN//AC-MCN solid-state ASC was reversibly charged/discharged at voltages as high as 1.8 V and possessed a remarkable volumetric capacity of 9.83 F cm −3 and an energy density of 4.25 mW h cm −3, as well as good cycle stability.